Prokaryotic bias in surface ocean particles - Yeongjun Ryu; Ashley E. Maloney; Victoria H. Luu; Lingkun Guo; Sergey Oleynik; Sarah E. Fawcett; Meytal B. Higgins; Nicolas Van Oostende; Bess B. Ward; Claire C. Z. Cook; Natalie R. Cohen; Erica Ewton; et al. (Proceedings of the National Academy of Sciences, 2026)
While the ocean’s photosynthetic production of organic matter rivals that on land, a combination of heterotrophy and sinking prevents significant accumulation of particulate organic matter (POM) in open ocean surface waters. The origins and fates of POM in ocean surface waters are unclear, in part due to the dominance of nonliving, altered material. From the natural nitrogen isotopic composition of chlorophyll and its degradation products, we estimate the fraction of particles from eukaryotic vs. prokaryotic phytoplankton. In subtropical gyres and along the eastern North Pacific margin, the eukaryotic-to-prokaryotic ratio in particles matches that of living phytoplankton. However, in the North Atlantic outside its subtropical gyre, particles have a lower eukaryotic-to-prokaryotic ratio than do the living phytoplankton. This discrepancy at least partly arises from preferential sinking of eukaryotic biomass, consistent with the canonical but disputed paradigm that cyanobacteria disproportionately fulfill the energetic demands of the upper ocean microbial community while eukaryotes drive export production. The prokaryotic bias in surface ocean particles may also result from slow decomposition of specific components of prokaryotic biomass, a possible bottleneck in the ocean’s microbial loop. The different fates of organic matter produced by eukaryotic and prokaryotic phytoplankton affect the productivity of the surface ocean, carbon export to the interior, and the signals recorded in deep-sea sediments.